Kombinasi Metode Pembobotan Entropy dan Grey Relational Analysis dalam Pemilihan Pelanggan Terbaik - Handoko, Dwi (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2024)
The best customers are individuals or groups who not only consistently make purchases, but also show high loyalty to a company's products or services. The purpose of the research of the combination of Entropy and GRA weighting methods in selecting the best customers is to use a more objective and accurate approach in evaluating customers based on various relevant criteria. By utilizing the Entropy method, this study aims to objectively determine the weight of the criteria, based on the variation of customer assessment data. Once the criteria weights are determined, the GRA is used to analyze the relationship between the customer and the ideal solution, so that it can identify the customer closest to the best customer profile. The results of the best customer ranking show that Customer 2 occupies the top position with a value of 0.17819, indicating that this customer has the best performance in meeting the specified criteria. Followed by Customer 6 who obtained a value of 0.17794, which also showed excellent performance. The results of this ranking provide clear insights into customer profiles and can be the basis for formulating better strategies in customer relationship management.